Design and development of an IoT-based coolant top-up automation system to enhance productivity and cost efficiency in machining prosses - Al Faruq, Muhammad Sholih Faiz; Kristianto, Stevanus Brian; Kesawa, I Gusti Nyoman; Purwoko, Yohanes P Agung; Novita Anggraini W; Beny Hermawan; Danang Wahyudi; Yudistara, Selamat (JTTM : Jurnal Terapan Teknik Mesin, 2026)
PT XYZ experiences inefficiencies in the coolant top-up process during machining operations, which is currently performed manually. This method is time-consuming and icreases the risk of damage to cutting tools and machines, therby contributing to higher maintenance costs. To address this issue, a system capable of assisting the coolant top-up process as well as to enable rapid and real-time monitoring the coolant quality and quantity is required in order to prevent tool damage and reduce maintenance cost. Using an 8 Step Methodology, an automatic coolant top-up system for machining processes was developed based on Internet of Things(IoT) technology with real time data acquisition and transmission. Experimental results show that the system improvestime efficiency by 80 %, reduce coolant consumption by 8 %, and increases cutting tool eficiency by for type D (driiling) , 6 % for type IN (tapping) and 20 % for type C (milling). These results demonstrate that the system effectively enhances operational efficiency and reduces costs in machining process. The innovative contribution of this study lies in the integration of low-cost IoT components with a cloud-based spreadsheet platform for real-time monitoring and control, making the system easy to implement, scalable and cost-effective for coolant management in machining operations.